On the importance of borrowing constraints for house price dynamics - Essi Eerola; Niku Määttänen (Bank of Finland, 2008)
We study how a household borrowing constraint the the form of a down payment requirement affects house price dynamics in an OLG model with standard preferences. We find that in certain situations the borrowing constraint shapes house price dynamics substantially. The importance of the constraint depends very much on whether house price changes are driven by interest rate or aggregate income shocks. Moreover, because of the borrowing constraint, house price dynamics display substantial asymmetries between large positive and large negative income shocks. These results are related to the fact that the share of borrowing-constrained households is different following different shocks.
URN:NBN:fi:bof-20140807500
Keywords: E21; R21; 330; house prices; dynamics; borrowing constraints; down payment constraint